Pengaruh Disiplin Kerja Dan Pengawasan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT Mitra Unggul Pusaka Segati Kecamatan Langgam - Anggi Lestari; Raden Lestari Garnasih; Nuryanti Nuryanti (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The purpose of this study was to determine the effect of work discipline and supervision on employee performance with job satisfaction as an intervening variable. This study took the location at PT. Mitra Unggul Pusaka Segati, Langgam District, with a total of 104 respondents. In this study consists of four variables. These variables are Employee Performance (Y2), Job Satisfaction (Y1), Work Discipline (X1), Supervision (X2). The data analysis method uses a quantitative descriptive method with the Path Analysis tool, with the help of SPSS version 23. The results of the study show that: 1) Work Discipline has a positive and significant effect on job satisfaction at PT. Mitra Unggul Pusaka Segati, Langgam District. 2) Supervision has a positive and significant effect on job satisfaction at PT. Mitra Unggul Pusaka Segati, Langgam District. 3) Work discipline has a positive and significant effect on employee performance at PT. Mitra Unggul Pusaka Segati, Langgam District. 4) Supervision has a positive and significant effect on employee performance at PT. Mitra Unggul Pusaka Segati, Langgam District. 5) Job satisfaction has a positive and significant effect on employee performance at PT. Mitra Unggul Pusaka Segati, Langgam District. 6) Work Discipline has a positive and significant effect on employee performance through job satisfaction at PT. Mitra Unggul Pusaka Segati, Langgam District. 7) Supervision has a positive and significant effect on employee performance through job satisfaction at PT. Mitra Unggul Pusaka Segati, Langgam District.